Mutations at palmitylation sites of the influenza virus hemagglutinin affect virus formation. - Zurcher, T (J Virol, 1994)
The carboxy terminus of the hemagglutinin (HA) of influenza A viruses contains three cysteine residues which are highly conserved among HA subtypes. It has previously been shown for the H2, H3, and H7 subtypes of HA that these cysteine residues are modified by the covalent attachment of palmitic acid. In order to study the role of the acylated cysteines in the formation of infectious influenza viruses, we introduced mutations into the HA of influenza A/WSN/33 virus (H1 subtype) by reverse-genetics techniques. We found that the cysteine at position 563 of the cytoplasmic tail is required for infectious-particle formation. The cysteine at position 560 can be changed to alanine or tyrosine to yield virus strains that are attenuated in cell cultures. The change from cysteine at position 553 to serine or alanine does not significantly alter the phenotype of the virus. The requirement for a cysteine at position 563 suggests a functional role for palmitylation of the cytoplasmic tail. This interpretation is further supported by experiments in which two or more of the cysteine residues were mutated, eliminating potential palmitylation sites. None of these double or triple mutations resulted in infectious virus. Selection of revertants of the attenuated cysteine-to-tyrosine mutant (mutation at position 560) always resulted in reversion to cysteine rather than to other amino acids. Although our data indicate a biological role for the conserved cysteine residues in the cytoplasmic tail of the HA of influenza viruses, we cannot exclude the possibility that structural constraints in the cytoplasmic tail of the HA--rather than altered palmitylation--are the determining factors for infectious-particle formation. IMAGES: